Funnel : Catalogue 1984. (Toronto : The Funnel, 1984)
Anderson, David ; Baird, Rebecca ; Bendahan, Raphael ; Davis, Martha ; Doyle, Judith ; Fontana, Mikki ; Greenwald, Ric ; Hammer, Barbara ; MacLennan, Toby ; McLaren, Ross ; Meigs, Sandra ; etc.
Engels
boek